Site-specific protein labeling utilizing lipoic acid ligase (LplA) and bioorthogonal inverse electron demand Diels-Alder reaction - Baalmann, Mathis; Best, Marcel; Wombacher, Richard (Noncanonical amino acids, 2018)
Here, we describe a two-step protocol for selective protein labeling based on enzyme-mediated peptide labeling utilizing lipoic acid ligase (LplA) and bioorthogonal chemistry. The method can be applied to purified proteins, protein in cell lysates, as well as living cells. In a first step a W37V mutant of the lipoic acid ligase (LplAW37V) from Escherichia coli is utilized to ligate a synthetic chemical handle site-specifically to a lysine residue in a 13 amino acid peptide motif—a short sequence that can be genetically expressed as a fusion with any protein of interest. In a second step, a molecular probe can be attached to the chemical handle in a bioorthogonal Diels-Alder reaction with inverse electron demand (DAinv). This method is a complementary approach to protein labeling using genetic code expansion and circumvents larger protein tags while maintaining label specificity, providing experimental flexibility and straightforwardness.
Gesehen am 18.06.2020